BIOLOGICAL PRODUCT - BIOINSECTICIDE - F.S, Pulotov; K.F, Sayfiddinov (Journal of Medical Genetics and Clinical Biology, 2024)
In this article Bacillus thuringiensis var.thuringiensis on the bacterial strain thuringiensis Uzviti М №1, data are presented on the research work on the study of the insecticidal properties being carried out at the same time on the experimental series of the biological drug bioinsecticid, which was first prepared in a laboratory setting